WHEN TWO PANDEMICS COLLIDE: RACISM, COVID-19 AND THE ASSOCIATION OF BLACK SOCIAL WORKERS EMERGENCY RESPONSE - Thomas Bernard, Wanda (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2020)
In the spring of 2020, African Nova Scotians were faced with two emerging pandemics: the ongoing pandemic of anti-Black racism, and the pandemic of COVID-19. The Association of Black Social Workers created a response specific to the needs of African Nova Scotians, employing the six practice principles of Africentric social work. They established a partnership with community and government partners to manage a phone line to triage based on need, and a virtual community check-in to connect about the pressing Black Lives Matter movement. This paper contextualizes the historic and current systemic racial inequities faced by African Nova Scotians within the context of the current public health emergency, and the need for an equitable, community-based emergency response. This specialized, Africentric service provision model can be used to inform the development of emergency responses for other Black communities in Canada.